Comparative Functional Genomic Analysis of Two Vibrio Phages Reveals Complex Metabolic Interactions with the Host Cell - Skliros, Dimitrios; Kalatzis, Panos G.; Katharios, Pantelis; Flemetakis, Emmanouil (Frontiers in Microbiology, 2016)
Sequencing and annotation was performed for two giant double stranded DNA bacteriophages, φGrn1 and φSt2 of the Myoviridae family, considered to be of great interest for phage therapy against Vibrios in aquaculture live feeds. In addition, phage-host metabolic interactions and exploitation was studied by transcript profiling of selected viral and host genes. Comparative genomic analysis with other giant Vibrio phages was also performed to establish the presence and location of homing endonucleases highlighting distinct features for both phages. Phylogenetic analysis revealed that they belong to the “schizoT4like” clade. Although many reports of newly sequenced viruses have provided a large set of information, basic research related to the shift of the bacterial metabolism during infection remains stagnant. The function of many viral protein products in the process of infection is still unknown. Genome annotation identified the presence of several viral ORFs participating in metabolism, including a Sir2/cobB (sirtuin) protein and a number of genes involved in auxiliary NAD+ and nucleotide biosynthesis, necessary for phage DNA replication. Key genes were subsequently selected for detail study of their expression levels during infection. This work suggests a complex metabolic interaction and exploitation of the host metabolic pathways and biochemical processes, including a possible post-translational protein modification, by the virus during infection.